Method for preparing bottom sediment autoclaved building material based on directional growth of aluminum-substituted tobermorite
By introducing sulfonated lignin into the preparation of autoclaved aerated concrete (AAC) building materials, aluminum-substituted tobermorite is oriented to grow into plate-like crystals, solving the problems of low utilization rate and difficulty in morphology control of AAC, improving product strength and durability, and achieving efficient resource utilization.
Patent Information
- Application Number
- CN202611194993.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-11-06
AI Technical Summary
The existing technology for preparing autoclaved aerated concrete (AAC) building materials suffers from problems such as low utilization rate of sediment, low product strength, difficulty in controlling the morphology of aluminum-substituted tobermorite, limited functionality of existing additives, and interference of organic matter and humus in the sediment with the autoclaving reaction.
By introducing sulfonated lignin, a network of multifunctional materials with specific structure and function, and under specific autoclaving conditions, aluminum-substituted tobermorite is induced to grow into plate-like crystals. Organic matter interference is weakened by flocculation and dehydration pretreatment, thus constructing a dense hydration framework.
It significantly improves the compressive strength and durability of solid autoclaved bricks with bottom mud, meets the MU30 grade requirements, optimizes the pore structure, realizes high-value utilization of bottom mud with high admixture, and has both environmental and economic benefits.
Smart Images

Figure CN123041850A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of environmental remediation technology and relates to a method for preparing autoclaved aerated concrete (AAC) building materials. Background Technology
[0002] Dredging projects of rivers, lakes, reservoirs, and urban polluted water bodies generate large amounts of sediment annually. This sediment, with its high water content, fine particles, and complex composition, poses a significant challenge to water environment management due to its long-term storage or simple landfilling, as it not only occupies land but also risks pollutant diffusion. Rich in minerals such as SiO2 and Al2O3, this sediment can undergo a volcanic ash reaction with Ca(OH)2 under alkaline and autoclaved conditions to produce hydration products such as CSH gel and tobermorite, providing the basic conditions for preparing autoclaved building materials. Tobermorite (Ca5Si6O) 16 (OH)₂·4H₂O) is one of the most important hydrated crystalline phases in autoclaved silicate products. Its layered crystal structure consists of repeating silicon-oxygen tetrahedral ternary chains and calcium-oxygen octahedral single chains. Al dissolved from the sediment... 3+ It can replace Si in tobermorite silicon-oxygen tetrahedra. 4+ This process forms aluminum-substituted tobermorite, which is the core cementitious phase for improving the strength of autoclaved bricks. However, under traditional processes, aluminum-substituted tobermorite often exists in a disordered fibrous or needle-like form, with numerous intercrystalline pores and high material porosity, which restricts the improvement of brick strength. If aluminum-substituted tobermorite can be directionally grown and arranged in a dense, layered manner, it is expected to significantly reduce capillary porosity, optimize pore size distribution, and significantly improve the material's mechanical properties and impermeability.
[0003] At present, the preparation of autoclaved aerated concrete (AAC) building materials mainly has the following technical problems: (1) The utilization rate of the sediment is low and the strength of the product is low. The traditional process is simple mixing, which makes it difficult to exert the cementitious activity of the silica-alumina components in the sediment. The strength of autoclaved products is mostly MU15-MU20 or A3.5 grade, which is difficult to meet the requirements of load-bearing walls. Although adding a large amount of cement can improve the strength, it increases the cost and weakens the economic and environmental benefits of resource utilization. (2) The morphology of aluminum replacing tobermorite is difficult to control. Under the traditional autoclaving process, the crystals are mostly arranged in a disordered fibrous or needle-like shape, which makes it difficult to form a dense hydration skeleton. The product has a loose pore structure and high capillary porosity, which limits the improvement of strength and leads to durability problems such as high water absorption and low softening coefficient. (3) Existing additives have a single function. Lignin materials are mostly used as water-reducing agents or dispersants. Their molecular structure lacks the synergistic effect of a three-dimensional network skeleton and dual active functional groups, and cannot be used as a crystal growth template to induce the directional growth of platy tobermorite. (4) Organic matter and humus in the sediment interfere with the autoclaving reaction. They can be adsorbed on the surface of mineral particles to hinder ion dissolution and interfere with the crystallization of hydration products. Traditional pretreatment mainly focuses on simple dehydration and lacks targeted control measures, so the reactivity of the sediment cannot be fully utilized. Summary of the Invention
[0004] To address the problems in the preparation of autoclaved aerated concrete (AAC) building materials described in the background art, such as low utilization rate of AAC, low product strength, difficulty in controlling the morphology of aluminum-substituted tobermorite, limited functionality of existing additives, and interference of organic matter and humus in the AAC with the autoclaving reaction, this invention provides a method for preparing AAC based on the directional growth of aluminum-substituted tobermorite. This method introduces a network-like multifunctional material with specific structure and function, namely network-like sulfonated lignin, which, under specific autoclaving curing conditions, actively and controllably induces aluminum-substituted tobermorite to grow in an ideal layered morphology, thereby significantly improving the compressive strength of solid autoclaved bricks.
[0005] The preparation method of the present invention includes the following steps: S1. The bottom mud from the dredging project is subjected to flocculation and dewatering pretreatment to obtain dewatered mud material; pulp liquor and sulfonated lignin dispersion are prepared; the sulfonated lignin is a cross-linked three-dimensional network structure, and its molecular structure has sulfonic acid group and hydroxymethyl dual active functional group; S2. Weigh the raw materials according to the following mass percentages: 40%-60% dewatered cement, 15%-30% cement, 10%-25% fine sand, and 5%-15% calcium hydroxide; based on the total mass of the above raw materials, the mass percentage of pulp liquor is 4%-6%, and the mass percentage of sulfonated lignin dispersion is 0.2%-2.0%; mix the dewatered cement with cement, fine sand, calcium hydroxide, the pulp liquor, and the sulfonated lignin dispersion evenly to obtain a wet material; S3. After dehydrating the wet material, it is placed into a mold and pressure-formed to obtain a brick blank; S4. After static pre-curing, the brick blank is subjected to autoclaving. During the autoclaving process, the sulfonated lignin is used to induce the generation of aluminum-substituted tobermorite, and its directional growth is regulated into plate-like crystals. After natural curing, a solid autoclaved brick with a bottom mud is obtained.
[0006] This invention solves the following technical problems through a complete technical route: "introduction of sulfonated lignin with specific structure - induction of crystal-oriented growth during autoclaving - synergistic adaptation of sediment raw material system": I. Addressing the difficulty in controlling the morphology of aluminum-substituted tobermorite: This invention introduces sulfonated lignin with a cross-linked three-dimensional network structure and dual active functional groups of sulfonic acid and hydroxymethyl groups into the raw material system. During autoclaving, this material is used to induce the directional growth of aluminum-substituted tobermorite into plate-like crystals. The mechanism is as follows: In the initial stage of the hydrothermal reaction, the dual active functional groups of sulfonic acid and hydroxymethyl groups directionally enrich the Al dissolved from the sediment through complexation. 3+ and Ca 2+This process forms numerous uniformly dispersed crystal nucleation sites, preventing disordered crystal aggregation caused by local ion supersaturation. As the reaction proceeds, the three-dimensional network structure exerts a spatial template confinement effect. Simultaneously, the selective adsorption of aluminum by sulfonic acid groups replaces the advantageous growth crystal faces of tobermorite, inhibiting one-dimensional overgrowth of the crystals and inducing the crystals to transform from the traditional randomly arranged fibrous and needle-like morphology into a regular, oriented sheet-like structure. Ultimately, the sheet-like crystals interlock and overlap, constructing a dense hydration framework, significantly reducing the capillary porosity of the product and optimizing the pore size distribution. This fundamentally overcomes the defects of uncontrollable crystal morphology and loose pore structure under traditional processes.
[0007] II. Addressing the issues of low utilization rate and low product strength of bottom sediment: This invention uses 40%-60% dewatered material as the main silica-alumina raw material, combined with cement and calcium hydroxide to provide calcium components, and supplemented with fine sand and pulp. Under alkaline and autoclaving conditions, the silica-alumina components in the bottom sediment fully participate in the pozzolanic reaction. Because the dense hydration skeleton formed by the replacement of tobermorite with flake aluminum significantly enhances the bonding effect between particles, the product strength no longer depends on the addition of a large amount of cement. The resulting solid autoclaved bricks made from bottom sediment achieve a 7-day compressive strength of over 40 MPa and a 28-day compressive strength of over 60 MPa, meeting the requirements of MU30 grade in GB / T 11945-2019 "Autoclaved Lime-Sand Solid Bricks and Solid Blocks". While achieving high-volume and high-value utilization of bottom sediment, this invention breaks through the limitations of traditional bottom sediment autoclaved products in terms of strength grade, enabling the large-scale production of standard bricks, paving bricks, slope protection sponge blocks, and other load-bearing and functional building materials.
[0008] III. Addressing the issue of limited functionality in existing additives: This invention breaks through the traditional use of lignin materials as water-reducing agents or dispersants. It selects a specially designed network-like sulfonated lignin: its natural three-dimensional network molecular structure provides the spatial framework required for crystal growth, and the sulfonic acid groups (-SO3)... - The dual-functional group system of hydroxymethyl (-CH2OH) provides synergistic sites for ion complexation and selective adsorption on crystal faces. Together, they constitute the dual function of "functional group complexation nucleus + network template confinement induction", which is not available in ordinary lignin and commercial lignin sulfonates. Thus, for the first time, the directional regulation of the crystal morphology development of aluminum-substituted tobermorite was achieved by using lignin-based materials as crystal growth templates.
[0009] IV. Addressing the problem of organic matter and humus in the sediment interfering with the autoclaving reaction: In step S1 of this invention, the sediment from dredging projects undergoes flocculation and dewatering pretreatment. Through flocculation, fine particles and some organic components in the sediment are aggregated and separated, weakening their adsorption and coating on the surface of mineral particles and reducing their interference with ion dissolution and crystallization of hydration products. At the same time, after pretreatment, the sediment is stably blended into the raw material system at a high proportion of 40%-55%. Combined with the directional crystallization growth of aluminum replacing tobermorite under autoclaving conditions, the reactivity of the silica-alumina components in the sediment is fully utilized, ensuring the high-value utilization of the sediment from both pretreatment and reaction control perspectives.
[0010] In summary, this invention achieves the directional growth of aluminum-substituted tobermorite platy crystals and the construction of a dense hydration framework through the functional group complexation and spatial template induction of network sulfonated lignin. In conjunction with sediment flocculation pretreatment and raw material proportioning system, the strength, pore structure and durability of sediment autoclaved building materials are improved simultaneously, resulting in significant environmental benefits and engineering promotion value.
[0011] Furthermore, the dredging sediment, on a dry basis, has an organic matter content of less than 20 wt%, a humic matter content of less than 16 wt%, and an average particle size of less than 0.425 mm.
[0012] Further, in step S1, the flocculation and dewatering pretreatment specifically involves: preparing a flocculant with a mass concentration of 0.1%-0.3% using cationic polyacrylamide, mixing it evenly with the bottom mud from the dredging project, and then separating the mud and water and dewatering by pressure filtration to obtain a dewatered material with a water content of 45wt%-55wt%; the cationic polyacrylamide has an ionic degree of 20-40, a molecular weight of 8-10 million, and the fineness of the powdered polyacrylamide meets the requirement that the residue on a 40-mesh sieve is less than 1%, the softening temperature is 135-145℃, the apparent density is 0.35-0.65g / mL, and the decomposition temperature is 205-210℃.
[0013] Furthermore, the sulfonated lignin has a lignin content greater than 80%, an ash content less than 4%, and a sulfonation degree greater than 1.5 mmol / g; the sulfonated lignin dispersion is prepared by rapidly stirring sulfonated lignin powder with water, and has a mass concentration of 20%-40%.
[0014] Furthermore, in step S2, during mixing, the dewatered material, cement, fine sand and calcium hydroxide are first mixed and stirred, then the pulp liquid is added and stirred, and finally the sulfonated lignin dispersion is added and stirred; the Ca / Si molar ratio of the wet material is 0.7-1.3, and the Al / Si molar ratio is 0.05-0.35.
[0015] Further, the cement is silicate cement PC42.5; the calcium hydroxide is calcareous building quicklime, wherein MgO≤5wt%, (CaO+MgO)≥90wt%, SO3≤2wt%, free water≤2wt%, and 0.2mm sieve residue≤2wt%; the fine sand has a fineness modulus of 1.6-2.2, mud content≤5wt%, mud lump content≤2wt%, and chloride ion content≤0.06wt%; the pulp liquor is prepared from dried pulp raw materials with fiber length of 1.6-2.7mm by a pulping machine, and has a moisture content of 85wt%-90wt%.
[0016] Furthermore, in step S3, the dehydration is carried out by vacuum filtration to reduce the moisture content of the wet material to 30wt%-40wt% to obtain semi-dry material; the pressure of the pressure forming is 10-50MPa and the holding time is 5-60min.
[0017] Furthermore, in step S4, the temperature for static curing is 25℃, the humidity is 60%-85%, and the time is 10-30h. The static curing also includes a step of adjusting the moisture content of the brick blanks, controlling the moisture content of the brick blanks to 8%-18%. If the moisture content is lower than this range, it is replenished by misting water spraying or covering with a wet cloth. If it is higher than this range, the static curing time is extended or low-temperature pre-drying is carried out.
[0018] Furthermore, in step S4, the autoclaving process employs a segmented heating, constant temperature and pressure, and slow cooling process. The heating rate is 0.5-2.0℃ / min, the steam pressure is 0.5-2.5MPa, the constant temperature stage temperature is 160-210℃, and the autoclaving time is 6-16h. The natural curing temperature is 15-25℃, the humidity is 60%-85%, and the curing time is 20-30 days.
[0019] Furthermore, in the autoclaved product of the solid autoclaved brick, flake aluminum replaces tobermorite crystals and interlocks with each other to form a dense hydration skeleton. The total porosity of the brick is 10.6%-18.4%, the water absorption rate is 5.3%-8.9%, and the softening coefficient is 0.84-0.94.
[0020] Compared with the prior art, the present invention has the following advantages: (1) Inducing aluminum-substituted tobermorite to grow into flaky, oriented crystals and constructing a dense hydration framework: The core technology involves using sulfomethylated lignin to induce aluminum-substituted tobermorite to grow into flaky crystals during autoclaving. The sulfomethylated lignin has a cross-linked three-dimensional network structure, and its sulfonic acid group and hydroxymethyl dual-active functional group on its molecular structure directionally enrich the Al dissolved from the bottom mud through complexation in the early stage of the hydrothermal reaction. 3+ and Ca 2+This process forms a large number of uniformly dispersed crystal nucleation sites, avoiding disordered crystal aggregation caused by local ion supersaturation. During the reaction, the three-dimensional network structure exerts a spatial template confinement effect, selectively adsorbing the advantageous growth crystal faces of aluminum-substituted tobermorite with sulfonic acid groups, inhibiting one-dimensional overgrowth of crystals, and inducing them to transform from the randomly arranged fibrous and needle-like morphology under traditional processes into regular thin-plate directional growth. Finally, the plate-like crystals interlock and overlap to construct a dense hydration framework, solving the technical problem of difficult morphology control of aluminum-substituted tobermorite at the microstructural level. (2) Significantly improve the compressive strength of bricks: Relying on the dense cemented skeleton formed by the interlocking and overlapping of sheet aluminum replacing tobermorite, the cementing effect between the bottom mud particles is significantly enhanced. The 7-day compressive strength of the resulting solid autoclaved bricks can reach more than 40MPa, and the 28-day compressive strength can reach more than 60MPa, which meets the requirements of MU30 grade of GB / T 11945-2019 "Autoclaved Lime Sand Solid Bricks and Solid Blocks". This breaks through the limitation that the strength of traditional autoclaved bricks with bottom mud is mostly MU15-MU20 grade, and can meet the demand of load-bearing walls for high-strength building materials. (3) Optimize pore structure and improve product durability: The layered and dense stacking of lamellar crystals replaces a large number of micropores between the disordered fibrous crystals, effectively reducing the capillary porosity of the brick and optimizing the pore size distribution. The total porosity of the brick is 10.6%-18.4%, the water absorption rate is 5.3%-8.9%, and the softening coefficient is 0.84-0.94. This overcomes the defects of traditional bottom mud autoclaved products with high water absorption rate and low softening coefficient, and improves the product's impermeability and performance stability in humid environments. (4) Achieve high-volume and high-value utilization of bottom sediment: Flocculation and dewatering pretreatment of bottom sediment from dredging projects weakens the adsorption and coating of organic matter and humic substances on the surface of mineral particles through flocculation, reducing their interference with ion dissolution and crystallization of hydration products, so that the reactivity of silica-alumina components in the bottom sediment can be fully utilized; the amount of dewatered cement in the raw material system reaches 40%-55%, and the strength improvement does not depend on the large amount of cement added (the cement content is only 15%-30%). While ensuring the strength of the product, the cost of raw materials is controlled, realizing the large-scale and high-value utilization of bottom sediment, which has both environmental and economic benefits. (5) The process route is simple and feasible and suitable for large-scale production: The preparation method of the present invention only includes conventional processes such as bottom mud pretreatment, batching and mixing, dehydration and molding, static curing, autoclaving and natural curing. The steps are clearly connected and no complex equipment or harsh process conditions are required. It can produce a variety of building materials such as standard bricks, road bricks, and slope protection sponge blocks on a large scale, and has good engineering promotion value.
[0021] In summary, this invention pre-treats dredged sediment by flocculation and dewatering, then mixes it with cement, fine sand, calcium hydroxide, pulp, and sulfonated lignin dispersion in a specific ratio. The mixture is then dewatered, molded, statically cured, autoclaved, and naturally cured to produce solid autoclaved bricks. The sulfonated lignin has a cross-linked three-dimensional network structure with both sulfonic acid and hydroxymethyl functional groups. During autoclaving, through complexation nucleation and spatial template confinement, it induces aluminum-substituted tobermorite to grow into plate-like crystals that interlock and overlap, constructing a dense cemented skeleton. The resulting solid autoclaved bricks exhibit high compressive strength, low total porosity, low water absorption, and a high softening coefficient, achieving simultaneous improvement in the high-value utilization of sediment and the strength and durability of the finished products. Attached Figure Description
[0022] Figure 1 This is a SEM image of sulfonated lignin with a three-dimensional network molecular structure.
[0023] Figure 2 The images are SEM images of solid autoclaved bricks with bottom mud after 28 days of autoclaving. (a), (b), and (c) are solid autoclaved bricks with bottom mud prepared in Comparative Example 1 without the addition of sulfonated methylated lignin. (d), (e), and (f) are solid autoclaved bricks with bottom mud prepared in Example 2 with the addition of sulfonated methylated lignin. CSH is CSH gel, and Tobemorite is tobemorite. Detailed Implementation
[0024] To make the technical problems, technical solutions, and beneficial effects to be solved by this application clearer, the following detailed description is provided in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and are not intended to limit the scope of this application.
[0025] This invention provides a method for preparing autoclaved aerated concrete (AAC) building materials based on the directional growth of aluminum-substituted tobermorite. By introducing sulfonated lignin with specific functional groups as a crystal form regulator, the method induces aluminum-substituted tobermorite in the hydration products to grow into plate-like crystals along a specific direction, constructing a dense hydration framework. This significantly improves the mechanical strength and durability of the building materials, while also achieving a high resource utilization rate of the sediment. The method specifically includes the following steps: I. Raw material pretreatment and auxiliary material preparation Sediment pretreatment: Sediment from dredging projects is selected, primarily from river and lake dredging or sedimentation. The dry basis organic matter content is controlled to be <20wt%, humic matter content <16wt%, and average particle size <0.425mm. Cationic polyacrylamide (ionicity 20-40, molecular weight 8-10 million) is prepared into a flocculant solution with a mass concentration of 0.1%-0.3%, which is mixed with the sediment for 3-5 minutes for flocculation and sedimentation, effectively capturing sediment colloids and humic particles to achieve mud-water separation. After pressure filtration and dewatering, a dewatered material with a water content of 45wt%-55wt% is obtained. The powdered polyacrylamide has a fineness that meets the requirement of less than 1% residue on a 40-mesh sieve, a softening temperature of 135-145℃, an apparent density of 0.35-0.65g / mL, and a decomposition temperature of 205-210℃.
[0026] Excipient preparation: For sulfonated lignin, select sulfonated lignin powder with a lignin content >80% and a sulfonation degree >1.5 mmol / g, and quickly stir with water to prepare a dispersion with a mass concentration of 20%-40%. For example... Figure 1 As shown, this sulfonated lignin has a cross-linked three-dimensional network molecular structure. Figure 1 The spatial network structure exhibits a complex interweaving and entanglement, visually confirming that the material is not a nonlinear structure, but rather forms a rich three-dimensional porous network system. Obvious particle attachments or protrusions are visible on the surface of the network structure and at the skeleton connections. These microscopic features correspond to the active sites on its molecular structure: sulfonic acid groups and hydroxymethyl dual active functional groups, endowing the material with extremely strong adsorption and complexation capabilities. It is this special microscopic network structure that enables sulfonated lignin to play a crucial role in the preparation of autoclaved building materials: First, it induces directional growth. Under the high temperature and high pressure environment of autoclaving, the three-dimensional network structure can effectively adsorb onto specific crystalline surfaces of the hydration products (aluminum-substituted tobermorite), acting as a template and guide, inducing the originally randomly growing crystals to develop into a plate-like morphology. Second, it constructs a dense skeleton. Under the guidance of the network structure, the plate-like crystals interlock and overlap, ultimately constructing a dense cemented skeleton, thereby significantly optimizing the strength and durability of the bottom mud autoclaved bricks.
[0027] Its molecular structure is rich in sulfonic acid groups and hydroxymethyl groups, making it suitable for use as a crystal form inducer.
[0028] Pulp liquor: Dry pulp raw materials with fiber length of 1.6-2.7mm are selected and prepared into pulp liquor with a moisture content of 85wt%-90% by a pulping machine.
[0029] II. Ingredients and Mixing Weigh the raw materials according to the following mass percentages: 40%-60% dewatered cement, 15%-30% cement, 10%-25% fine sand, and 5%-15% calcium hydroxide. Furthermore, based on the total mass of the above raw materials, the pulp liquor accounts for 4%-6% of the total mass, and the sulfonated lignin dispersion accounts for 0.2%-2.0% of the total mass.
[0030] Specifically, the calcium hydroxide is a calcareous building slaked lime, conforming to the HCl requirements of JC / T 481-2013 "Building Slaked Lime," which requires MgO ≤ 5wt%, (CaO+MgO) ≥ 90wt%, SO3 ≤ 2wt%, free water ≤ 2wt%, and 0.2mm sieve residue ≤ 2wt%. HCl + MgO ≤ 5% thus confirms the calcium hydroxide as a calcareous building slaked lime, eliminating magnesium interference and its influence on the CSH crystal form. (CaO+MgO) ≥ 90% corresponds to HCl90, the highest purity among the three grades of calcareous building slaked lime, ensuring a stable Ca supply. 0.2mm sieve residue ≤ 2% ensures good dispersion of the slaked lime in wet materials, preventing it from competing with sulfonated lignin for active sites.
[0031] The fine sand conforms to the specifications in GB / T 14684-2011 "Sand for Construction," with a fineness modulus of 1.6-2.2, a mud content ≤5wt%, a clay lump content ≤2wt%, and a chloride ion content ≤0.06wt%. More specifically, the fine sand is selected from natural quartz fine sand with SiO2 ≥90% to avoid the aluminum-containing feldspar / mica minerals raising the Al / Si ratio from the 0.05-0.35 range, thus preventing the "aluminum substitution" of tobermorite from becoming "aluminum excess." Once aluminum is excessive, platy crystals cannot grow.
[0032] The mixing and stirring process is as follows: First, add the dewatered material, cement, fine sand, and calcium hydroxide to the mixer while stirring for about 5-10 minutes until homogeneous. Then, add the pulp liquid for wet mixing and stir for about 5-10 minutes. Finally, add the sulfonated lignin dispersion and stir thoroughly for about 5-10 minutes to obtain a homogeneous wet mixture. Control the final wet mixture's Ca / Si molar ratio to be 0.7-1.3 and the Al / Si molar ratio to be 0.05-0.35.
[0033] III. Molding and Blank Making The uniformly mixed wet material is passed through a three-stage vacuum filtration chamber to gradually remove water, reducing the moisture content to 30wt%-40%, resulting in a semi-dry material. This semi-dry material is then placed into a mold and pressed again through a pressure molding machine to remove water and form the material. The mold is then pressed at 10-50 MPa and held for 5-60 minutes to obtain a dense brick blank. When the semi-dry material is used for standard autoclaved bricks, the control conditions are that the pressed brick blank shows no bleeding, no corner chipping, and no obvious surface cracks. During pressing, the preferred pressure is 30-40 MPa; the preferred holding time is 10-30 minutes.
[0034] IV. Maintenance Process (1) Static curing: Place the brick blanks in an environment with a temperature of 25℃ and a humidity of 60%-85% for 10-30 hours; during this period, adjust the moisture content and control the moisture content of the brick blanks within the range of 8%-18%. If the moisture content of the brick blanks is too low, add water by misting or cover with a damp cloth to add moisture. If the moisture content of the brick blanks is too high, extend the static curing period or pre-dry at low temperature. This allows the brick blanks to complete the initial hydration, stabilize the structure of the blanks, and reduce internal stress.
[0035] (2) Autoclaving: The pre-cured brick blanks are placed in an autoclave for autoclaving, using a segmented process: Heating: Increase the temperature at a rate of 0.5-2.0℃ / min; Constant temperature and pressure: Curing at 160-210℃ and 0.5-2.5MPa steam pressure for 6-16 hours. During this stage, sulfonated lignin utilizes its three-dimensional network structure and dual active functional groups to specifically adsorb onto the crystal surface, inducing aluminum-substituted tobermorite to grow into plate-like crystals, forming an interlocking and overlapping microstructure.
[0036] Cooling: Slowly cool to room temperature before removing from the autoclave.
[0037] (3) Natural curing: The steam-pressed brick blanks are cured at 15-25℃ and 60%-85% humidity for 20-30 days to obtain the finished solid steam-pressed bricks with bottom mud.
[0038] The solid autoclaved bricks prepared by the above method exhibit a dense skeletal structure in their microstructure, where lamellar aluminum replaces tobermorite crystals. Macroscopic properties include a total porosity of 10.6%-18.4%, a water absorption rate of 5.3%-8.9%, and a softening coefficient as high as 0.84-0.94, demonstrating excellent physical and mechanical properties and durability. The 7-day compressive strength of these solid autoclaved bricks can reach over 40 MPa, and the 28-day compressive strength can reach over 60 MPa, exceeding the MU30 grade of the GB / T11945-2019 standard "Autoclaved Sand-Lime Solid Bricks and Solid Blocks".
[0039] The present invention will be further described below with reference to specific embodiments.
[0040] Example 1 This embodiment describes the preparation of solid autoclaved bricks with bottom mud, as detailed below.
[0041] (1) Pretreatment of bottom sediment: Bottom sediment from river and lake dredging projects was collected. The organic matter content was less than 20 wt%, the humic matter content was less than 16 wt%, and the average particle size was less than 0.425 mm, based on dry weight. Cationic polyacrylamide (ionic degree of 30, molecular weight of 9 million, and powder fineness meeting the requirement of less than 1% residue on a 40-mesh sieve) was prepared into a flocculant with a mass concentration of 0.2%, which was mixed evenly with the bottom sediment. After mud-water separation and pressure filtration dewatering, a dewatered material with a water content of 50 wt% was obtained.
[0042] (2) Preparation of pulp liquor and sulfonated lignin dispersion: Dry pulp raw materials with fiber length of 1.6-2.7 mm are prepared into a fluid pulp liquor with a moisture content of 85wt%-90wt% by a pulping machine; sulfonated lignin powder is added to water and stirred rapidly to prepare a sulfonated lignin dispersion with a mass concentration of 30%; the sulfonated lignin is a cross-linked three-dimensional network structure with a lignin content of more than 80%, an ash content of less than 4%, a sulfonation degree of more than 1.5mmol / g, and has sulfonic acid group and hydroxymethyl dual active functional group in its molecular structure.
[0043] (3) Ingredient mixing: Weigh the raw materials according to the mass ratio of dewatered material: cement: fine sand: calcium hydroxide = 55:25:12:8. Add 5% of the total mass of raw materials to the pulp, and the amount of sulfonated lignin is 0.5%. The cement is silicate cement PC42.5; the calcium hydroxide is calcareous building quicklime, MgO≤5wt%, (CaO+MgO)≥90wt%, SO3≤2wt%, free water≤2wt%, 0.2mm sieve residue≤2wt%; the fine sand has a fineness modulus of 1.6-2.2, mud content≤5wt%, mud lump content≤2wt%, and chloride ion content≤0.06wt%. During mixing, the dewatered material, cement, fine sand and calcium hydroxide are first mixed and stirred, then pulp liquid is added and stirred, and finally sulfonated lignin dispersion is added and stirred to obtain a uniformly mixed wet material; the water-to-solid ratio is controlled at 0.18, the Ca / Si molar ratio of the wet material is controlled at 0.7-1.3, and the Al / Si molar ratio is controlled at 0.05-0.35.
[0044] (4) Dehydration molding: The obtained wet material is vacuum filtered to reduce the moisture content to 35wt% to obtain semi-dry material; the semi-dry material is loaded into a mold and molded under pressure at 30MPa for 30min to obtain brick blank.
[0045] (5) Curing: The brick blanks are statically pre-cured for 20 hours at a temperature of 25℃ and a humidity of 60%-85%, and the moisture content of the brick blanks is controlled at 8%-18%. Then, they are placed in an autoclave and a process of segmented heating, constant temperature and pressure and slow cooling is adopted. The heating rate is 1.0℃ / min, the constant temperature stage temperature is 180℃, and constant temperature autoclaving is carried out for 8 hours. During the autoclaving process, sulfonated lignin induces aluminum-substituted tobermorite to grow into plate-like crystals. After the autoclaving is completed, the brick blanks are naturally cured for 28 days at a temperature of 15-25℃ and a humidity of 60%-85% to obtain solid autoclaved bricks with bottom mud.
[0046] Performance characterization: Tests showed that the brick sample in this embodiment had a 7-day compressive strength of 46.8 MPa, a 28-day compressive strength of 68.5 MPa, a flexural strength of 9.6 MPa, and a dry density of 1.82 g / cm³. 3 It has a water absorption rate of 8.9%, a softening coefficient of 0.84, and a total porosity of 18.4%. Figure 2 As shown in (d), (e), and (f), a large number of platy tobemorite crystals are generated in the autoclaved brick products. The crystals are well-developed, regularly arranged, and interlocked to form a dense hydration skeleton. CSH gel (CSH) fills the residual gaps between the platy crystals. The number of pores is small and the pore size is small, resulting in a dense overall structure.
[0047] Example 2 The difference between this embodiment and Embodiment 1 is that: the ratio of dewatered material:cement:fine sand:calcium hydroxide = 50:25:15:10, the sulfonated lignin content is 1.0%, the molding pressure is 35MPa, and the autoclaving system is constant temperature 190℃ for 10h. The other raw materials, process steps and parameters are the same as in Embodiment 1.
[0048] Performance characterization: 7-day compressive strength is 53.4 MPa, 28-day compressive strength is 79.2 MPa, flexural strength is 12.5 MPa, and dry density is 1.91 g / cm³. 3 It has a water absorption rate of 6.8%, a softening coefficient of 0.91, and a total porosity of 13.2%.
[0049] Example 3 The difference between this embodiment and Embodiment 1 is that: the ratio of dewatered material:cement:fine sand:calcium hydroxide = 45:30:15:10, the sulfonated lignin content is 1.5%, the molding pressure is 35MPa, and the autoclaving system is constant temperature 200℃ for 12h. All other aspects are the same as in Embodiment 1.
[0050] Performance characterization: 7-day compressive strength is 58.6 MPa, 28-day compressive strength is 86.4 MPa, flexural strength is 14.0 MPa, and dry density is 1.96 g / cm³. 3It has a water absorption rate of 5.9%, a softening coefficient of 0.93, and a total porosity of 11.8%.
[0051] Example 4 The difference between this embodiment and Embodiment 1 is that: the ratio of dewatered material:cement:fine sand:calcium hydroxide = 52:23:15:10, the sulfonated lignin content is 0.8%, the molding pressure is 35MPa, and the autoclaving system is constant temperature 190℃ for 10h. All other aspects are the same as in Embodiment 1.
[0052] Performance characterization: 7-day compressive strength is 55.2 MPa, 28-day compressive strength is 82.0 MPa, flexural strength is 13.1 MPa, and dry density is 1.93 g / cm³. 3 It has a water absorption rate of 6.4%, a softening coefficient of 0.90, and a total porosity of 12.6%.
[0053] Example 5 The difference between this embodiment and Embodiment 1 is that: the ratio of dewatered material:cement:fine sand:calcium hydroxide = 55:25:15:5, the sulfonated lignin content is 1.2%, the molding pressure is 40MPa, and the autoclaving system is constant temperature 185℃ for 12h. All other aspects are the same as in Embodiment 1.
[0054] Performance characterization: 7-day compressive strength is 49.5 MPa, 28-day compressive strength is 74.8 MPa, flexural strength is 11.4 MPa, and dry density is 1.89 g / cm³. 3 It has a water absorption rate of 7.5%, a softening coefficient of 0.88, and a total porosity of 15.1%.
[0055] Example 6 The difference between this embodiment and Embodiment 1 is that: the ratio of dewatered material:cement:fine sand:calcium hydroxide = 48:15:22:15, the sulfonated lignin content is 1.0%, the molding pressure is 35MPa, and the autoclaving system is constant temperature 190℃ for 10h. All other aspects are the same as in Embodiment 1.
[0056] Performance characterization: 7-day compressive strength is 45.0 MPa, 28-day compressive strength is 66.5 MPa, flexural strength is 10.8 MPa, and dry density is 1.85 g / cm³. 3 It has a water absorption rate of 8.1%, a softening coefficient of 0.87, and a total porosity of 17.2%.
[0057] Example 7 The difference between this embodiment and Embodiment 1 is that: the ratio of dewatered material:cement:fine sand:calcium hydroxide = 52:20:15:13, the sulfonated lignin content is 1.0%, the molding pressure is 35MPa, and the autoclaving system is constant temperature 190℃ for 10h. All other aspects are the same as in Embodiment 1.
[0058] Performance characterization: 7-day compressive strength is 51.6 MPa, 28-day compressive strength is 77.5 MPa, flexural strength is 12.0 MPa, and dry density is 1.90 g / cm³. 3 It has a water absorption rate of 6.9%, a softening coefficient of 0.90, and a total porosity of 13.7%.
[0059] Example 8 The difference between this embodiment and Embodiment 1 is that: the ratio of dewatered material:cement:fine sand:calcium hydroxide = 40:25:25:10, the sulfonated lignin content is 0.8%, the molding pressure is 35MPa, and the autoclaving system is constant temperature 185℃ for 10h. All other aspects are the same as in Embodiment 1.
[0060] Performance characterization: 7-day compressive strength is 43.2 MPa, 28-day compressive strength is 63.8 MPa, flexural strength is 10.1 MPa, and dry density is 1.86 g / cm³. 3 It has a water absorption rate of 8.3%, a softening coefficient of 0.86, and a total porosity of 18.0%.
[0061] Example 9 The difference between this embodiment and Embodiment 1 is that: the ratio of dewatered material:cement:fine sand:calcium hydroxide = 50:25:15:10, the sulfonated lignin content is 1.0%, the water-to-solid ratio is 0.16, the molding pressure is 40MPa, and the autoclaving system is constant temperature 200℃ for 12h. All other aspects are the same as in Embodiment 1.
[0062] Performance characterization: 7-day compressive strength is 60.5 MPa, 28-day compressive strength is 88.6 MPa, flexural strength is 15.2 MPa, and dry density is 2.00 g / cm³. 3 It has a water absorption rate of 5.3%, a softening coefficient of 0.94, and a total porosity of 10.6%.
[0063] Example 10 The difference between this embodiment and Embodiment 1 is that: the ratio of dewatered material:cement:fine sand:calcium hydroxide = 55:23:10:12, the sulfonated lignin content is 1.0%, the water-to-solid ratio is 0.14, the molding pressure is 35MPa, and the autoclaving system is a constant temperature of 190℃ for 10h. All other aspects are the same as in Embodiment 1.
[0064] Performance characterization: 7-day compressive strength is 52.6 MPa, 28-day compressive strength is 78.1 MPa, flexural strength is 12.2 MPa, and dry density is 1.91 g / cm³. 3 It has a water absorption rate of 6.6%, a softening coefficient of 0.90, and a total porosity of 13.4%.
[0065] Comparative Example 1 The difference between this comparative example and Example 2 is that no sulfonated lignin dispersion is added to the ingredients, i.e., the amount of sulfonated lignin is 0. The proportions of other raw materials (dehydrated material: cement: fine sand: calcium hydroxide = 50:25:15:10), water-to-solid ratio (0.18), molding pressure (35 MPa), and autoclaving regime (constant temperature 190°C, 10 h) are the same as in Example 2.
[0066] Performance characterization: 7-day compressive strength is 39.8 MPa, 28-day compressive strength is 58.6 MPa, flexural strength is 7.8 MPa, and dry density is 1.76 g / cm³. 3 It has a water absorption rate of 11.5%, a softening coefficient of 0.76, and a total porosity of 24.5%. Figure 2 As shown in (a), (b), and (c), in bricks without added sulfomethylated lignin, the hydration products are mainly flocculent, amorphous CSH gel (CSH), with only a small amount of fibrous or needle-like tobermorite randomly distributed between the gel and particles. The crystals are incompletely developed, disordered, and have obvious pores between particles, resulting in a loose structure.
[0067] Comparative Example 2 The difference between this comparative example and comparative example 1 is that: an equal amount of ordinary lignin is used to replace sulfonated lignin, with an admixture amount of 1.0%, while the other raw materials, process steps and parameters are the same as those in comparative example 1.
[0068] Performance characterization: 7-day compressive strength is 42.1 MPa, 28-day compressive strength is 62.4 MPa, flexural strength is 8.3 MPa, and dry density is 1.78 g / cm³. 3 The water absorption rate is 10.2%, the softening coefficient is 0.78, and the total porosity is 22.8%. Ordinary lignin lacks sulfonic acid and hydroxymethyl dual active functional groups in its molecular structure and does not possess a cross-linked three-dimensional network spatial framework. It cannot form uniform crystal nucleation sites through complexation, nor can it exert a spatial template confinement effect. Therefore, its control effect on the crystal morphology of tobermorite is weak, and the brick performance is close to that of Comparative Example 1.
[0069] Comparative Example 3 The difference between this comparative example and Comparative Example 1 is that an equal amount of commercial lignin sulfonate is used to replace sulfonated lignin, with an admixture amount of 1.0%. The other raw materials, process steps and parameters are the same as those in Comparative Example 1.
[0070] Performance characterization: 7-day compressive strength is 48.0 MPa, 28-day compressive strength is 70.6 MPa, flexural strength is 10.4 MPa, and dry density is 1.84 g / cm³. 3The water absorption rate was 8.4%, the softening coefficient was 0.85, and the total porosity was 17.5%. Although commercial lignin sulfonate contains sulfonic acid groups, which can play a certain role in dispersion and complexation, its molecular structure has not been optimized for cross-linking, lacks a three-dimensional network framework and the synergistic effect of sulfonic acid groups and hydroxymethyl groups, and cannot effectively induce the directional growth of platy tobermorite. Although the brick performance is better than that of Comparative Example 1 and Comparative Example 2, it is still significantly lower than that of the examples with the same dosage.
[0071] Comparative Example 4 The difference between this comparative example and Example 2 is that: after the brick blank is formed, it is not subjected to autoclaving. After static pre-curing, it is directly placed under the conditions of temperature 15-25℃ and humidity 60%-85% for natural curing for 28 days. The other raw materials (sulfonated methylated lignin content 1.0%), process steps and parameters are the same as in Example 2.
[0072] Performance characterization: 7-day compressive strength is 28.6 MPa, 28-day compressive strength is 45.2 MPa, flexural strength is 6.1 MPa, and dry density is 1.71 g / cm³. 3 The water absorption rate is 13.8%, the softening coefficient is 0.72, and the total porosity is 29.6%. Due to the lack of autoclaved hydrothermal conditions, the pozzolanic reaction between the silica and alumina components and the calcareous components in the bottom mud is low, making it difficult to form a tobermorite crystalline phase in the system. The hydration products are mainly low-crystallinity CSH gel, and even the addition of sulfomethylated lignin cannot exert its crystal morphology regulation effect. The brick strength and durability are the lowest.
[0073] The performance test results of Examples 1-10 and Comparative Examples 1-4 are summarized in Table 1, as shown below.
[0074] Table 1 Summary of performance of examples and comparative samples Based on the content of Examples 1-10 and Comparative Examples 1-4 above, the data in Table 1, and... Figure 2 The SEM morphology characterization results show that: (1) The 28-day compressive strength of Examples 1-10 is 63.8-88.6 MPa, which is far greater than GB / T The water absorption rate, softening coefficient, and freeze-thaw performance of the present invention meet the requirements of the MU30 grade of the standard 11945-2019 "Autoclaved Lime Sand Solid Bricks and Solid Blocks". This indicates that the present invention can stably prepare high-strength solid autoclaved bricks with bottom mud within a wide parameter range of 0.5%-1.5% sulfonated lignin content and 40%-60% bottom mud content. Under the same mix ratio and autoclaving regime, Example 2 (28-day compressive strength 79.2 MPa) is 35.2%, 26.9%, and 12.2% higher than Comparative Example 1 (28-day compressive strength 58.6 MPa), Comparative Example 2 (28-day compressive strength 62.4 MPa), and Comparative Example 3 (28-day compressive strength 70.6 MPa), respectively. This confirms that only sulfonated lignin with both cross-linked three-dimensional network structure and sulfonic acid group and hydroxymethyl dual active functional group can effectively induce aluminum-substituted tobermorite flake directional growth. (2) Comparison Figure 2 (a)-(c) and Figure 2 As can be seen from (d) to (f), after the addition of sulfonated lignin, the hydration products of the brick body changed from disordered flocculent gel and fibrous crystals to well-developed, interlocking and overlapping plate-like tobermorite crystals. The formation of a dense hydration skeleton reduced the total porosity of the brick body from 24.5% to 10.6%-18.4%, and the water absorption rate and softening coefficient were improved simultaneously. The mechanism of performance improvement was verified from the microstructure. (3) Comparative Example 4 shows that autoclaving hydrothermal conditions are a necessary prerequisite for the formation and directional control of tobermorite. The best-performing Example 9 (28-day compressive strength of 88.6 MPa) has a strength that is 96% higher than that of Comparative Example 4 (28-day compressive strength of 45.2 MPa). This proves that the present invention achieves the synergistic effect of ion complexation, spatial confinement and directional control of tobermorite through sulfonated lignin and combined with a suitable autoclaving regime, thus realizing the simultaneous improvement of the strength, pore structure and durability of autoclaved building materials of sediment, providing a reliable technical path for the large-scale high-value resource utilization of sediment.
[0075] The preferred embodiments of the present invention have been described in detail above with reference to the accompanying drawings and specific examples. However, the present invention is not limited to the specific details in the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.
Claims
1. A method for preparing autoclaved aerated concrete (AAC) building materials based on the directional growth of aluminum-substituted tobermorite, characterized in that, Includes the following steps: S1. Pre-treat the bottom mud of the dredging project by flocculation and dewatering to obtain dewatered mud material; prepare pulp liquor and sulfonated methylated lignin dispersion; The sulfonated lignin has a cross-linked three-dimensional network structure and its molecular structure has two active functional groups: sulfonic acid group and hydroxymethyl group. S2. Weigh the raw materials according to the following mass percentages: 40%-60% dewatered cement, 15%-30% cement, 10%-25% fine sand, and 5%-15% calcium hydroxide; based on the total mass of the above raw materials, the mass percentage of pulp liquor is 4%-6%, and the mass percentage of sulfonated lignin dispersion is 0.2%-2.0%; mix the dewatered cement with cement, fine sand, calcium hydroxide, the pulp liquor, and the sulfonated lignin dispersion evenly to obtain a wet material; S3. After dehydrating the wet material, it is placed into a mold and pressure-formed to obtain a brick blank; S4. After static pre-curing, the brick blank is subjected to autoclaving. During the autoclaving process, the sulfonated lignin is used to induce the generation of aluminum-substituted tobermorite, and its directional growth is regulated into plate-like crystals. After natural curing, a solid autoclaved brick with a bottom mud is obtained.
2. The preparation method according to claim 1, characterized in that: The dredging and sediment from the project has an organic matter content of less than 20 wt%, a humic matter content of less than 16 wt%, and an average particle size of less than 0.425 mm, based on a dry basis.
3. The preparation method according to claim 1, characterized in that: In step S1, the flocculation and dewatering pretreatment specifically involves: preparing a flocculant with a mass concentration of 0.1%-0.3% using cationic polyacrylamide, mixing it evenly with the bottom mud from the dredging project, and then separating the mud and water and dewatering by pressure filtration to obtain a dewatered material with a water content of 45wt%-55wt%; the cationic polyacrylamide has an ionic degree of 20-40 and a molecular weight of 8 million-10 million.
4. The preparation method according to any one of claims 1-3, characterized in that: The sulfonated lignin has a lignin content greater than 80%, an ash content less than 4%, and a sulfonation degree greater than 1.5 mmol / g; the sulfonated lignin dispersion is prepared by rapidly stirring sulfonated lignin powder with water, and has a mass concentration of 20%-40%.
5. The preparation method according to claim 4, characterized in that: In step S2, the dewatered material, cement, fine sand and calcium hydroxide are first mixed and stirred, then the pulp liquid is added and stirred, and finally the sulfonated lignin dispersion is added and stirred; the Ca / Si molar ratio of the wet material is 0.7-1.3 and the Al / Si molar ratio is 0.05-0.
35.
6. The preparation method according to claim 1, characterized in that: The cement is silicate cement PC42.5; the calcium hydroxide is calcareous building quicklime, wherein MgO≤5wt%, (CaO+MgO)≥90wt%, SO3≤2wt%, free water≤2wt%, and 0.2mm sieve residue≤2wt%; the fine sand has a fineness modulus of 1.6-2.2, mud content≤5wt%, mud lump content≤2wt%, and chloride ion content≤0.06wt%; the pulp liquor is prepared from dried pulp raw materials with fiber length of 1.6-2.7mm by a pulping machine, and has a moisture content of 85wt%-90wt%.
7. The preparation method according to claim 1, characterized in that: In step S3, the dehydration is carried out by vacuum filtration to reduce the moisture content of the wet material to 30wt%-40wt% to obtain semi-dry material; the pressure of the pressure forming is 10-50MPa and the holding time is 5-60min.
8. The preparation method according to claim 1, characterized in that: In step S4, the temperature for static curing is 25℃, the humidity is 60%-85%, and the time is 10-30h. The static curing also includes a step of adjusting the moisture content of the brick blanks, controlling the moisture content of the brick blanks to 8%-18%. If the moisture content is lower than this range, it is replenished by misting water spraying or covering with a wet cloth. If it is higher than this range, the static curing time is extended or low-temperature pre-drying is carried out.
9. The preparation method according to claim 1 or 8, characterized in that: In step S4, the autoclaving adopts a segmented heating, constant temperature and pressure and slow cooling process. The heating rate is 0.5-2.0℃ / min, the steam pressure is 0.5-2.5MPa, the constant temperature stage temperature is 160-210℃, and the autoclaving time is 6-16h. The natural curing temperature is 15-25℃, the humidity is 60%-85%, and the curing time is 20-30 days.
10. The preparation method according to claim 1, characterized in that: In the autoclaved product of the solid autoclaved bricks with bottom mud, flake aluminum replaces tobermorite crystals and interlocks with each other to form a dense hydration skeleton. The total porosity of the brick body is 10.6%-18.4%, the water absorption rate is 5.3%-8.9%, and the softening coefficient is 0.84-0.94.
